Bilateral Dentate Gyrus Structural Alterations in a Cat Associated With Hippocampal Sclerosis and Intraventricular Meningioma. (November 2015) - Klang, A.; Thaller, D.; Schmidt, P.; Kovacs, G. G.; Halasz, P.; Pakozdy, A.
A 13-year-old cat had a history of seizures for 3 years that resembled temporal lobe epilepsy. Histologic examination of the brain revealed bilateral hippocampal alterations, including hypergyration and broadening of the dentate gyrus associated with hippocampal sclerosis and an intraventricular meningioma near the hippocampal region. The findings in the dentate gyrus were interpreted as a congenital malformation; however, it could not be ruled out that the alterations were induced by the seizures. Similar changes of the dentate gyrus have not been previously described in cats.